Effects of Geometric Isomerism and Anions on the Kinetics and Mechanism of the Stepwise Formation of Long-Range DNA Interstrand Cross-Links by Dinuclear Platinum Antitumor Complexes - Zhang, Junyong (2008)
Reported herein is a detailed study of the kinetics and mechanism of formation of a 1,4-GG interstrand cross-link by the dinuclear platinum anticancer compound [(15)N][{cis-PtCl-(NH(3))(2)}(2){μ-NH(2)(CH(2))(6)NH(2)}](2+) (1,1/c,c (1)). The reaction of [(15)N]1 with 5′-{d(ATATGTACATAT)(2)} (I) has been studied by [(1)H,(15)N] HSQC NMR spectroscopy in the presence of different concentrations of phosphate. In contrast with the geometric trans isomer (1,1/t,t), there was no evidence for an electrostatic preassociation of 1,1/c,c with the polyanionic DNA surface, and the pseudo-first-order rate constant for the aquation of [(15)N]1 was actually slightly higher (rather than lower) than that in the absence of DNA. When phosphate is absent, the overall rate of formation of the cross-link is quite similar for the two geometric isomers, occurring slightly faster for 1,1/t,t. A major difference in the DNA binding pathways is the observation of phosphate-bound intermediates only in the case of 1,1/c,c. 15 mm phosphate causes a dramatic slowing in the overall rate of formation of DNA interstrand cross-links due to both the slow formation and slow closure of the phosphate-bound monofunctional adduct. A comparison of the molecular models of the bifunctional adducts of the two isomers shows that helical distortion is minimal and globally the structures of the 1,4 interstrand cross-links are quite similar. The effect of carrier ligand was investigated by similar studies of the ethylenediamine derivative [(15)N]1-en. A pK(a) value of 5.43 was determined for the [(15)N]1,1/c,c-en diaquated species. The rate of reaction of [(15)N]1-en with duplex I is similar to that of 1,1/c,c and the overall conformation of the final adduct appears to be similar. The significance of these results to the development of “second-generation” polynuclear platinum clinical candidates based on the 1,1/c,c chelate (dach) series is discussed.